ENGLISH SPEAKING SKILL: IMPLICATION TO THE PROFESSIONAL NURSES - Daar, Gabriel Fredi (Wawasan Kesehatan, 2016)
English language skill has been a need for the sake of written and oral communication purposes. One of the skills that is supposed to posses is English speaking skill. it is the ability of using English accurately and fluently. This artcle is aimed at describing the use of English speaking skill owned by proffesional nurses and its implications to nursing practices. Proffesional nurses are the user of this language either. English speaking skill is used in the context of therapeutic relationship between nurses and patients in the efforts to communicate problems and initiate healing through appropritae diagnosis. Therefore, proffesional nurses are demanded to learn English. Learning is emphazised on specific materials implemented in nursing field (English for specific purpose). Skill and mastery of nursing terms in English are necessarily possessed in order to be ale to plan and undertake ideal and effective model of communication and treatment to patients